Queer Methods and Methodologies Intersecting Queer Theories and Social Science Research - Browne, Kath; Nash, Catherine J. (Taylor & Francis, 2010)
This interdisciplinary volume provides the first systematic consideration of the implications of a queer perspective in the pursuit of social scientific research. It will appeal to anyone pursing research at the intersections between social scientific research and queer perspectives, as well as those engaging with methodological considerations in social science research more broadly